How quantitatively important is public investment for both business cycle fluctuations and output growth in Bulgaria (1999-2018)? - Aleksandar Vasilev (Macroeconomics and Finance in Emerging Market Economies, 2020)
We introduce government investment into a real-business-cycle setup. We calibrate the model to Bulgarian data for the period 1999-2018. We then proceed to quantitatively evaluate the effect of the public capital accumulation channel as a tool for business cycle propagation, as well the importance of public investment spending on output growth. Government investment shocks, in the absence of other technological disturbances, turn out to be unable to account for observed business cycles in Bulgaria. On the other hand, government investment may be able to increase subsequent output growth, but that effect is estimated to be quite small.
Keywords: E32; 330; business cycles; government investment; Bulgaria